INTEGRATION OF THE VALUES OF JUSTICE, BENEFIT, ND LEGAL CERTAINTY IN ARRANGEMENT LAND ACQUISITION FOR PUBLIC INTEREST - Silvy Vebritha; Widaningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Improvement need infrastructure public make procurement land as room sensitive between mandate development and protection right constitutional citizens ; because that , the settings No Enough understood legally -formally, but rather must based on integration mark justice , benefit and certainty law . Research This aim formulate as well as testing the evaluation model operations that ensure third mark present consistent in every stages — planning , preparation , implementation , and delivery results — in framework law positive Indonesia. The method used is enriched juridical -normative approach socio -legal, with the unit of analysis covers material primary law (UUD 1945, UUPA, UU 2/2012, PP 19/2021, and regulations implementer ) and material secondary published ; data analyzed in a way grammatical , systematic , and teleological , then mapped to indicator operational : participation meaning and mechanism objection ( justice ), rationality interest general and efficiency procedural ( benefit ), as well as procedure transparent , documented , and can tested ( certainty law ). The results show framework normative Actually adequate , but there is gap implementation on quality participation , formulation compensation that has not been accommodate non-material losses , and inconsistencies documentation and a resolution forum disputes at the level area . In conclusion , integration most effective value realized as a checklist cross binding stage​ actors , flow , deadlines , and document formats standard ; certainty drafted laws​ Good become prerequisite presence justice substantive and achievable benefits public . Implications practically covering need Operational regulations , digitalization​ system information land For transparency and audit trail , strengthening team coordination cross agencies , as well as supervision participatory for legitimacy social and fluency project public can improved in a way sustainable research​ support the development agenda index integration grades and studies comparative cross area for measuring performance as well as perfect design policy based proof in a way national measurable